حياةُ الشيخِ إبراهيمَ الدسوقي: دراسةٌ شاملةٌ لسيرتهِ وتعاليمهِ وإرثهِ الروحي: The Life of Sheikh Ibrahim al-Dasuqi: A Comprehensive Study of His Biography, Teachings, and Spiritual Legacy (Al-Qamar, 2026)
This study explores the life of Sheikh Ibrahim al-Desouqi – may Allah have mercy on him – highlighting his significant contributions to Islamic knowledge and scholarship. The research examines his early life, education, and scholarly journey, emphasizing his role in spreading religious and intellectual knowledge. It also reflects on his personal qualities, virtues, and influence on students and the broader Muslim community, presenting him as one of the great scholars of his era. The study aims to provide a comprehensive understanding of Sheikh al-Desouqi’s life, his intellectual legacy, and the spiritual and ethical values he imparted to future generations.
Keywords: Sheikh Ibrahim al-Desouqi, biography, intellectual legacy, spiritual values, Muslim scholar